2021
DOI: 10.1186/s42269-021-00544-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro gastrointestinal digestion of a bisdemethoxycurcumin-rich Curcuma longa extract and its oral bioavailability in rats

Abstract: Background Nonetheless curcumin has potential health benefits, its low bioavailability limits the application of conventional turmeric extract with curcumin as major curcuminoid. This is a comparative study to assess the stability, bioaccessibility and biological activity of BDMC in standardized C. longa extract (REVERC3) relative to curcumin in regular turmeric extract (RTE). Here we report the preparation of a standardized Curcuma longa extract (REVERC3™) standardized to contain 75 ± 5 w/w % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…These disadvantages are overcome by BDMC, which differs from DMC and curcumin by lack of o-methoxy groups on its phenolic rings. Sudeep et al examined the gastrointestinal digestion of BDMC and curcumin in male rats and reported significantly higher bioavailability of BDMC, with a 4.4-fold higher plasma concentration than that of curcumin (18). Moreover, the antioxidant capacity of BDMC was superior to that of curcumin at the same concentration (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These disadvantages are overcome by BDMC, which differs from DMC and curcumin by lack of o-methoxy groups on its phenolic rings. Sudeep et al examined the gastrointestinal digestion of BDMC and curcumin in male rats and reported significantly higher bioavailability of BDMC, with a 4.4-fold higher plasma concentration than that of curcumin (18). Moreover, the antioxidant capacity of BDMC was superior to that of curcumin at the same concentration (18).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, lipid-soluble, small, and non-polar molecules tend to pass through the round window membrane more readily (25). BDMC is the most stable in non-polar solvents of the curcuminoids (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] However, these medications do not possess disease-modifying properties. [8,9] Furthermore, undesirable side effects have also been observed in treatments using these medications. [8,9] Therefore, searches for new natural AChE inhibitors from natural resources as potent drug seeds are still conducted, and several natural compounds with AChE inhibitory activity have been reported, including huperzine, [12] a possible treatment agent for AD, as well as tomatine, [13] berberine, [14] palmatine, and jatrorrhizine.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are reports studying the anti-inflammatory and anticancer properties of DMC and BDM [ 31 , 32 ]. In turn, evidence indicates DMC and BDM possess the same drawbacks compromising CUR’s bioavailability [ 33 , 34 ]. Hence, these two curcuminoids are promising molecules for the improvement of their limited bioavailability through PLHNs.…”
Section: Introductionmentioning
confidence: 99%